Frontiers in bacteriology: Challenges and opportunities - Mylonakis, Eleftherios (Frontiers in Bacteriology, 2023)
It is a Frontiers tradition to herald the start of a new journal with an editorial that highlights the challenges and opportunities of the relevant field. For Frontiers in Bacteriology, the start of the journal coincides with a pivotal era for the field, with the slow-moving epidemic of antimicrobial resistance threatening medical progress.